Housing Cost Burden, Material Hardship, and Well-Being. Issue 3 (4th May 2022) - Shamsuddin, Shomon; Campbell, Colin
ABSTRACT: Millions of households face housing affordability problems as house prices and rents rise faster than incomes. Yet little is known about how high housing expenditures affect well-being. Using data from the Survey of Income and Program Participation, we examine the relationship between housing cost burden, material hardship, and residential satisfaction after the Great Recession. We find that households with higher housing cost burdens were more likely to experience some form of material hardship, controlling for other variables. The probability of material hardship increased with cost burden for households spending up to 50% of their income on housing. However, households that spend more than half of their income on housing are no more likely to experience material hardship than households who spend around 50%. We find some evidence that families with children trade high housing costs for improvements in housing conditions. The findings provide empirical support for using housing cost burden as a measure of affordability and suggest higher housing cost burdens may contribute to decreased well-being through multiple forms of material hardship but also may have threshold effects.